Enhancing Student Mobility in Higher Education: A Case Study on Application Architecture and Digital Services Supporting Processes and Transactions - Strahonja, Vjeran; Pažur Aničić, Katarina; Oletić Tušek, Izabela (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Enabling student mobility within higher education involves complex, interconnected processes that are supported by various digital tools and applications. This study focuses on these processes at the University of Zagreb, Faculty of Organization and Informatics, conducting a detailed case study to analyse the existing digital services that facilitate student mobility. It aims to define and discuss the application architecture of an integrated system and explore how these services can be further developed by integrating legacy components, open services, and open-source elements. The proposed application architecture should support basic transactions, workflows and the need for data storage and analysis, thereby enhancing system interoperability and simplifying processes for all stakeholders involved—including students, international relations officers, and academic advisors. By proposing further digitalisation, this paper contributes to simplifying and improving of the mobility process, making it more accessible and efficient for the international education community.